Hierarchy and Authority in a Dynamic Perspective : A Model Applied to Donor Financing of NGO Proposals - Yontcheva, Boriana (IMF Working Papers; Working Paper ;, 2003)
This paper presents a dynamic game of strategic delegation between a principal and an agent. The principal can choose between two organizational designs: a traditional hierarchy where she retains authority over the choice of projects to be implemented or a delegation where she allows her agent to select the project. The key objectives of this model are to identify the long-run determinants of the principal's choice and verify the impact of the authority allocation on the agent's effort levels and on the principal's payoffs. We apply the model to the relationships between institutional donors and nongovernmental organizations.